Analiza możliwości zagospodarowania złóż węgla brunatnego w rejonie Gubina ze szczególnym uwzględnieniem uwarunkowań lokalnych (przyrodniczych, społecznych, kulturowych) = Analysis of environmental, social and cultural conditions of lignite extraction in Gubin region - Naworyta, Wojciech; Chodak, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The work describes analysis of local conditions of lignite extraction from the deposit Gubin. The deposit has been characterized and restrictions for mining due to quality of soils, natural values and nature protection have been presented.
Keywords: węgiel brunatny; ochrona środowiska; społeczność lokalna; lignite; environment protection; local society